The efficacy of Acorus calamus L. crude extract formulated in bentonite nanoparticles against Crocidolomia pavonana (Lepidoptera:Pyralidae) - Purwatiningsih; Indarti, Dwi (Future Science, 2023)
The prospect of A. calamus extract to be botanical insecticides to control the insect pests is very promising. The insect control properties of the A. calamus are predominantly to have β-asarone, saponin and flavonoid. However, there are some factors limiting their efficacy. Short release rate at the point contact, the inherent volatility and vulnerability to oxidation and ultra-violet light are causing phytochemical changes during the application. Thus developing nanotechnology to increase their efficacy studied in this research. To develop the plant extract in nanoformulation, experiment on adsorption and desoption capacity were carried out with Acorus extract treated bentonite substrate analysed by GC techniques. In addition, to investigate the effectiveness of the plant extract treated bentonite were evaluated on Crocidolomia pavonana. Third instar larvae were used in the evaluation of antifeedant effect by using no choice methods. The results showed that Bentonite nanoparticles was effective in controlling the release of a bioactive element. Purifed clay bentonite for getting Na-bentonite increased the specific surface area of material therefore increased the adsorption site on the clay layer of the material. Crude extract of A.calamus can dissolve well in combination of water and organic solvents. Desorption experiments proved that Na-bentonite released more slowly than raw clay bentonite. Purification of bentonite to Na-bentonite resulted the changing of phytochemical properties bentonite which lead to an increase in the adsorption capacity of bentonite. In term of antifeedant evaluation based on damage to cabbage leaves seedling, the least damage was observed on leaves with nanoparticle plant extract formulation. The antifeedant index of A. calamus in nanoparticles formulation showed 25% higher that untreated cabbage plant seedling. The glasshouse trial was conducted to evaluate their efficacy on cabbage seedling. However, the brown leaves or phytotoxic effect has been found by the time the extracts nano formulation has been sprayed.